Targeting non-coding RNA family members with artificial endonuclease XNAzymes - Maria J. Donde; Adam M. Rochussen; Saksham Kapoor; Alexander I. Taylor (Communications Biology, 2022)
Engineered RNA endonuclease XNAzymes can specifically target individual disease-associated non-coding RNAs (ncRNAs) in vitro with potential as platform technology for precision detection or knockdown of individual microRNAs or longer ncRNAs.